The Fear of Missing Out Phenomenon Among FISIP UGJ Students on Instagram Social Media - Oktaviani, Anggeliqua; Syahfirna, Talia; Noviana, Wina; Nurfalah, Farida (CV. Media Digital Publikasi Indonesia, 2025)
In today's rapidly evolving technological landscape, social media has become a primary means of spending time by following others' lives and activities. One of the factors contributing to the phenomenon of Fear of Missing Out (FoMo) is the use of social media platforms. Among the various options available, Instagram has emerged as the top choice for the general public. This globally popular app offers various features for updating videos or photos, including the Instastory feature, which is filled with users' daily activities. From there, as viewers, we often feel anxious and compare our lives with others who seem happier or more interesting. This study aims to identify FoMo trends among FISIP UGJ students on Instagram. The method used in this study is qualitative, employing techniques such as interviews, observation on Instagram, and documentation. The informants in this study consist of five students selected using purposive sampling. The results of the study indicate that the FoMo phenomenon among FISIP UGJ students is identified through several trends, namely fashion, location, cuisine, and self-branding, with a primary focus on the location trend.